PENGARUH DISIPLIN KERJA, MOTIVASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI PRODUKTIVITAS KERJA KARYWAN SEBAGAI VARIABEL MEDIASI DI HOTEL SARI PACIFIC JAKARTA - Suci Lestari; Meylani Tuti (LPPM Universitas Asa Indonesia, 2019)
Purpose- In any organization, both for profit and non-profit entities, Human Resources is very important. This study aims to examine the effect of work discipline, motivation and compensation on employee performance through work productivity at the Sari Pacific Hotel Jakarta. Design/methodology/approach- The sample involved was 250 people with a nonprobability sampling method from Sari Pacific Hotel Jakarta. The data of this study were obtained from distributing questionnaires. This research uses data validity test, reliability test with Alpha Cornbach coefficient, transforming data using MSI (Method of Successive Interval) technique, Malahanobies Distance Test. Classic assumption test, path analysis, normality test, multicollinearity test, linearity test, heterokedasticity test, path coefficient test, correlation analysist, mediation testing with sobel test and determination coefficient test to determine the effect either direct or indirrect between work discipline, motivation and compensation for employee performance through productivity as variables mediation. Based on testing the validity and reliability with Alpha Cronbach, the data is valid and reliabel. Findings- The results of this study are work discipline, motivation and compensation partially have a positive affect on work productivity, directly. Work productivity directly affects employee performance. Work discipline, motivation and compensation partially affect indirectly on employee performance through work productivity as a mediating variable.